Magnetic resonance imaging changes with recombinant human interferon-beta-1a: a short term study in relapsing-remitting multiple sclerosis. Issue 3 (September 1996) - Pozzilli, C; Bastianello, S; Koudriavtseva, T; Gasperini, C; Bozzao, A; Millefiorini, E; Galgani, S; Buttinelli, C; Perciaccante, G; Piazza, G; Bozzao, L; Fieschi, C
Abstract : OBJECTIVE: To evaluate whether recombinant human interferon-beta-1a significantly affects disease activity as measured by a reduction in the number and volume of Gd enhancing lesions on monthly MRI. The study also evaluated the effect on six-monthly T2 weighted abnormality and relapse frequency. METHODS: After a baseline scan and a six month pretreatment period, 68 patients were randomly assigned to receive either 3 MIU or 9 MIU of interferon-beta-1a by subcutaneous injection three times a week for six months. All patients were examined by Gd enhanced MRI every month in both pretreatment and treatment periods. The evaluation of Gd enhancing lesions was performed blind at the end of the study. RESULTS: The mean number of Gd enhancing lesions was higher during the pretreatment period than during treatment. This difference was statistically significant for the two different dose subgroups (3.5 v 1.8, P < 0.001 for the 3 MIU group and 2.4 v 0.9, P < 0.001 for the 9 MIU group, corresponding to a reduction of 49% and 64% respectively). The mean volume of Gd enhancing lesions also significantly decreased by 61% (3 MIU group) and 73% (9 MIU group). These reductions were evident only after the first month of treatment. The six-monthly rate of new lesions as seen in T2 weighted images showed a similar trend of reduction with treatment (65% and 70% respectively). Lesion volume on T2 scans significantly increased during the pretreatment period whereas it remained almost stable during the treatment period in both groups. Clinical relapse rate was significantly reduced by treatment (53% for the 3 MIU group, P < 0.001; 69% for the 9 MIU group, P < 0.001). CONCLUSION: Interferon-beta-1a seemed effective in reducing disease activity in relapsing-remitting multiple sclerosis at both the doses used.